A Review of ex vivo Elemental Mapping Methods to Directly Image Changes in the Homeostasis of Diffusible Ions (Na+, K+, Mg2 +, Ca2 +, Cl–) Within Brain Tissue - Hartnell, David; Andrews, Wendy; Smith, Nicole; Jiang, Haibo; McAllum, Erin; Rajan, Ramesh; Colbourne, Frederick; Fitzgerald, Melinda; Lam, Virginie; Takechi, Ryusuke; Pushie, M. Jake; Kelly, Michael E.; et al. (Frontiers in Neuroscience, 2020)
Diffusible ions (Na+, K+, Mg2+, Ca2+, Cl–) are vital for healthy function of all cells, especially brain cells. Unfortunately, the diffusible nature of these ions renders them difficult to study with traditional microscopy in situ within ex vivo brain tissue sections. This mini-review examines the recent progress in the field, using direct elemental mapping techniques to study ion homeostasis during normal brain physiology and pathophysiology, through measurement of ion distribution and concentration in ex vivo brain tissue sections. The mini-review examines the advantages and limitations of specific techniques: proton induced X-ray emission (PIXE), X-ray fluorescence microscopy (XFM), secondary ion mass spectrometry (SIMS), laser-ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), and the sample preparation requirements to study diffusible ions with these methods.